A novel solidification model considering undercooling effect for metal based low temperature latent thermal energy management. (February 2019) - Soni, Vikram; Kumar, Arvind; Jain, V.K.
Highlights: A novel convection-diffusion based solidification model with undercooling effects. A detailed validation of non-equilibrium and equilibrium solidification models. Analysis of thermal and flow behavior, and energy discharged in a metal PCM based TEM system. Study suggests the importance of undercooling during discharging stage in a metal PCM. Abstract: A numerical study of solidification process of a metal phase change material during the energy discharge stage considering non-equilibrium undercooling effect is performed for low-temperature latent thermal energy management (TEM) system. A multi-dimensional convection-diffusion algorithm for non-equilibrium solidification is proposed. In the model, the solidification interface velocity is based on undercooled kinetic solidification, which is subsequently used for solid fraction calculation using an interface tracking method. The model is validated with the benchmark experimental data. The solidification behavior obtained from the conventional and the proposed solidification models are compared. The conventional model failed to capture the solidification characteristics arising from the undercooling effects. The proposed model successfully captures various stages of solidification, namely liquid cooling, undercooling, kinetic solidification and recalescence, and solid cooling. The influence of undercooling on the coupled heat transfer and fluid flow behavior during solidification is described. An interesting flow reversal behavior is noticed at an early stage of nucleation. The energy discharged is found to be slower with the undercooling effects than that predicted by the conventional model. The results provide insights for metal based TEM system in the temperature range of 10 °C–50 °C where the energy discharged is affected due to undercooling.